Helicid Reverses Lipopolysaccharide‐Induced Inflammation and Promotes GDNF Levels in C6 Glioma Cells through Modulation of Prepronociceptin. Issue 7 (17th June 2020) - Zhang, Yuanxiang; Luan, Di; Liu, Yanhao; Li, Hongjin; Dong, Jian; Zhang, Xiaotong; Yuan, Lili; Zhong, Zhengling; Jiang, Lan; Li, Xuyi; Ye, Mingquan; Tong, Jiucui
Abstract: Helicid suppresses inflammatory factors and protects nerve cells in the hippocampus of rats with depression, but the mechanisms underlying its protective effects are unclear at present. In this investigation, we conducted gene silencing, Helicid intervention and rescue experiments to explore the protective actions of PNOC, the prepronociceptin gene known to regulate inflammatory processes, and Helicid on a C6 cell model of inflammation induced by LPS. Collective data from Western blots, ELISA, immunofluorescence and flow cytometry experiments showed that PNOC silencing or administration of Helicid led to reduced inflammatory factor levels, oxidative stress and expression of glial fibrillary acidic protein (GFAP), along with increased glial cell lines‐derived neurotrophic factor (GDNF) expression. Furthermore, expression of p‐Akt in the Akt signaling pathway was increased. Interestingly, overexpression of PNOC in the Helicid treatment group partially reversed the Helicid‐induced changes in the above biochemical indexes. Our collective results provide strong evidence of Helicid‐mediated regulation of the Akt signaling pathway through PNOC to improve cell inflammation and oxidative stress. Abstract :